2018
DOI: 10.1038/s41598-018-23571-4
|View full text |Cite
|
Sign up to set email alerts
|

Microbiota Composition May Predict Anti-Tnf Alpha Response in Spondyloarthritis Patients: an Exploratory Study

Abstract: Spondyloarthritis (SpA) pathophysiology remains largely unknown. While the association with genetic factors has been established for decades, the influence of gut microbiota is only an emerging direction of research. Despite the remarkable efficacy of anti-TNF-α treatments, non-responders are frequent and no predictive factors of patient outcome have been identified. Our objective was to investigate the modifications of intestinal microbiota composition in patients suffering from SpA three months after an anti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
50
2
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(54 citation statements)
references
References 63 publications
(59 reference statements)
1
50
2
1
Order By: Relevance
“…Previous study of RA patients before and after synthetic disease-modifying anti-rheumatic drug treatment revealed moderate differences in the gut microbiota composition, with the perturbed microbial composition being party restored following treatment 72 . Similarly, analysis of spondylarthrosis patients before and after TNFi therapy also revealed modest differences in microbial composition yet no specific taxon was found to be modulated, likely due to sample size 73 . Utilising a larger sample size, we confirmed that TNFi therapy was correlated with a restoration of the perturbed microbial composition, and additionally identified several notable bacterial species modulated by treatment.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Previous study of RA patients before and after synthetic disease-modifying anti-rheumatic drug treatment revealed moderate differences in the gut microbiota composition, with the perturbed microbial composition being party restored following treatment 72 . Similarly, analysis of spondylarthrosis patients before and after TNFi therapy also revealed modest differences in microbial composition yet no specific taxon was found to be modulated, likely due to sample size 73 . Utilising a larger sample size, we confirmed that TNFi therapy was correlated with a restoration of the perturbed microbial composition, and additionally identified several notable bacterial species modulated by treatment.…”
Section: Discussionmentioning
confidence: 98%
“…There has also been suggestive evidence reported that the gut microbiome is associated with differences in AS disease activity 17 . In addition, one study compared SpA patients’ stool samples before and three months after TNF-inhibitor (TNFi) treatment onset 18 . Although modest changes were found in microbiome alpha-diversity measures after TNFi treatment, no changes in specific bacterial taxa were observed.…”
Section: Introductionmentioning
confidence: 99%
“…In axial SpA, patients who improved with TNFi had a stable microbiome, which was less prone to perturbations with treatment. Additionally, patients who responded to TNFi tended to have higher taxa diversity prior to treatment .…”
Section: Discussionmentioning
confidence: 99%
“…Before anti‐TNF administration, a higher proportion of Burkholderiales (Proteobacteria) in future responder patients was identified by this study. This suggests an interaction between anti‐TNF treatment and intestinal microbiota even if further studies are needed …”
Section: Role Of Microbiota and Efficacy Of Therapeutics In Jiamentioning
confidence: 99%
“…This suggests an interaction between anti-TNF treatment and intestinal microbiota even if further studies are needed. 94 A recent study, also performed in adult patients with rheumatoid arthritis, enrolled 42 patients divided according to current therapy: 11 patients were naïve to immunosuppressants, 11 patients were receiving methotrexate, 10 patients were receiving the anti-TNF agent etanercept, and 10 patients were receiving etancercept plus methotrexate. Ten healthy subjects were used as controls.…”
Section: Microbiota and Jia Susceptibilitymentioning
confidence: 99%